Microbiome and human health (Henry Stewart Talks, 2025)
Human microbiome definition and composition, Main microbial groups and their functions, Microbiome role in health, Diet, lifestyle, and environment influence, Consequences of microbiome imbalance (dysbiosis), Strategies to restore healthy microbiome